2017
DOI: 10.3389/fmars.2016.00276
|View full text |Cite
|
Sign up to set email alerts
|

Colonial Tube-Dwelling Ciliates Influence Methane Cycling and Microbial Diversity within Methane Seep Ecosystems

Abstract: In a variety of marine ecosystems, microbial eukaryotes play important ecological roles; however, our knowledge of their importance in deep-sea methane seep ecosystems is limited. Microbial eukaryotes have the potential to influence microbial community composition and diversity by creating habitat heterogeneity, and may contribute to carbon cycling through grazing or symbiotic associations with microorganisms. In this study, we characterized the distribution, substrate variability and ecology of a particular g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…It has been previously shown that the benthic prokaryotic community was driven partially by the grain size composition of the sediment ( Dang et al, 2010 ). Benthic microbial eukaryotes are composed of heterotrophic groups, including ciliates and heterotrophic nanoflagellates, that prey on prokaryotes ( Fenchel, 1978 ; Pasulka et al, 2017 ). Thus, the changes of prokaryotic communities due to grain size composition might further influence the grazers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that the benthic prokaryotic community was driven partially by the grain size composition of the sediment ( Dang et al, 2010 ). Benthic microbial eukaryotes are composed of heterotrophic groups, including ciliates and heterotrophic nanoflagellates, that prey on prokaryotes ( Fenchel, 1978 ; Pasulka et al, 2017 ). Thus, the changes of prokaryotic communities due to grain size composition might further influence the grazers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in tidal flats, diatoms form a major component of microphytobenthos on sediments and are major players in nutrient cycling and provide a food resource to larger grazers ( Lohrer et al, 2004 ; Evrard et al, 2012 ). Generally, the abundances of sediment bacteria are several orders of magnitude higher than those in the pelagic environments ( Rublee, 1982 ), so do the bacterial productions ( Starink et al, 1996 ), and grazing of heterotrophic microbial eukaryotes (e.g., heterotrophic nanoflagellates and ciliates) on bacteria was proposed to be the primary cause of bacterial mortality ( Fenchel, 1978 ; Pasulka et al, 2017 ). In addition, the abundances of some groups of microbial eukaryotes, e.g., nanoflagellates and ciliates, may even exceed those of the overlaying sea water ( Wickham et al, 2000 ; Meng et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MMG2 bacteria have been reported from other marine hosts based on 16S rRNA and pmoA gene sequencing, although their abundances appear to generally be considerably lower than in the Campeche sponges (Supplementary Figures S3 and S4). MMG2-related sequences were described from ciliates collected at methane seeps along the eastern Pacific coast (1.7–9.7% of the ciliate bacterial community based on 16S rRNA tag sequencing) [63], and the squat lobster Shinkaia crosnieri from hydrothermal vents off Japan (1.7–12.0% of 16S rRNA clones), [64]. MMG2 sequences were also found in two sponge species: (i) an unidentified poecilosclerid sponge from seeps in the Gulf of Mexico that is morphologically distinct from our samples [28], and (ii) Cladorhiza methanophila from mud volcanoes off Barbados (16–25% based on 16S rRNA tag sequencing [25]).…”
Section: Resultsmentioning
confidence: 99%
“…The extent of the tube worm clumps is ∼140 m by ∼90 m, elongate parallel to the axis. The nearest vent fauna to the active chimneys are mats ( Figure 9F) of blue ciliate Eufolliculina caerulea (Pasulka et al, 2017), and white limpets Lepidodrilus fucensis on hydrothermal crusts consisting mainly of amorphous silica and clays or of barite.…”
Section: Sea Cliff Hydrothermal Sitementioning
confidence: 99%